Climate Change Impact Assessment Model on Corporate Financial Performance: A Data-Based and Analytical Approach - Akkapin, Supaphorn; Achmad Doradjat, Tubagus (CV. Lafadz Jaya, 2025)
Climate change has a significant impact on corporate financial performance worldwide. This study develops a model for assessing the financial impacts of climate change on corporate performance using a data-driven and analytical approach. The model integrates both physical and transitional risks caused by climate change and analyzes their effects on corporate financial metrics, such as profitability, operational costs, and market value. Through regression analysis, climate change scenarios, and Monte Carlo simulations, this research demonstrates that companies failing to anticipate climate change face substantial financial risks, while companies that adapt, such as those investing in low-carbon technologies, can reap long-term benefits. This study provides valuable insights for companies to manage climate risks and capitalize on opportunities arising from the transition to a low-carbon economy. Thus, it offers an approach that can help businesses plan and take strategic actions to mitigate the financial impacts of climate change.